Relasi Sistem Waris Matrilineal dan Akses Pendidikan Anak Laki-laki di Kabupaten Malaka: Analisis Sosio-Kultural - Asikin, Hasibun (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2025)
This study analyzes the relationship between the matrilineal inheritance system and boys' access to education in Malacca Regency, East Nusa Tenggara. In this region, Tetun customs position women as the main heirs of family wealth, while men hold different social roles. This study aims to explore how inheritance distribution affects boys' educational support during modern social change. The research method used was a qualitative approach with in-depth interview techniques with 15 informants, consisting of traditional leaders, parents, and school-age boys, as well as analysis of customary documents and field observations. The findings show that although boys traditionally do not get a share of inheritance of land or traditional houses, families still allocate resources for their education as a form of family social investment. However, male roles that tend to be directed outside the nuclear family (matriline) create ambivalence in long-term support. The study concludes that the customary inheritance system not only determines the distribution of wealth, but also shapes patterns of gender roles that impact access to education. The implication is that regional education policies need to consider the cultural context as part of the strategy of equitable access to education.